Analysis of Knowledge, Attitudes and Behavior of SMAN 13 Padang Students Regarding Stunting - Ilona, Sandra; Erin Desweni; Dian eka Nursyam (CV. CENDIKIA JENIUS INDONESIA, 2026)
Stunting remains a major public health problem in Indonesia, and its prevention requires early intervention, including among adolescents as future parents and productive generations. Adolescents play a strategic role in shaping long-term health and nutritional behaviors; therefore, understanding their knowledge, attitudes, and behaviors toward stunting is essential. This study aimed to describe the knowledge, attitudes, and behaviors of students at SMA Negeri 13 Padang regarding stunting. A descriptive study with a cross-sectional design was conducted. A total of 100 students were selected using an accidental sampling technique. Data were collected between November and December 2024 using a structured questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate analysis with frequency and percentage distributions. The results showed that most respondents had good knowledge of stunting (87%) and positive attitudes toward stunting prevention (68%). However, preventive behaviors were predominantly categorized as moderate (45%) and were not fully aligned with the level of knowledge possessed. This study concludes that a gap exists between knowledge, attitudes, and preventive behaviors related to stunting among adolescents. Therefore, continuous school-based educational interventions focusing on behavioral change are recommended to strengthen stunting prevention efforts from an early age.